Професор Одеського університету Олександр Сухов (1881-1944 pp.): нові дані про останні роки життя - Петровський, Е. (З архівів ВУЧК-ГПУ-НКВД-КГБ, 2004)
The present article, based on the new found documents, reconstructed the last period of biography of professor Oleksandr Sukhov (1881–1944), the author of works in the feilds of economic and physical geography, statistics, oriental studies, biology and botany, history of revolutionary movement. The conditions of his arrests in 1923 and 1938 as well as the course of investigation, sentence and death in the Siberia (by that time he had already served sentence”) were found out.